Live-high train-low improves repeated time-trial and Yo-Yo IR2 performance in sub-elite team-sport athletes - Inness, M. W. H.; Billaut, F.; Aughey, R. J. (Journal of Science and Medicine in Sport, 2017)
Objectives: To determine the efficacy of live-high train-low on team-sport athlete physical capacity and the time-course for adaptation. Design: Pre-post parallel-groups. Methods: Fifteen Australian footballers were matched for Yo-Yo Intermittent recovery test level 2 (Yo-YoIR2) performance and assigned to LHTL (n = 7) or control (Con; n = 8). LHTL spent 19 nights (3 × 5 nights, 1 × 4 nights, each block separated by 2 nights at sea level) at 3000-m simulated altitude (FIO2: 0.142). Yo-Yo IR2 was performed pre and post 5, 15, and 19 nights. A 2- and 1-km time-trial (TT) was performed pre and post intervention. Haemoglobin mass (Hbmass) was measured in LHTL after 5, 10, 15, and 19 nights. A contemporary statistical approach using effect size, confidence limits, and magnitude-based inferences was used to measure changes between groups. Results: Compared to pre, Hbmass was possibly higher after 15 (3.8%, effect size (ES) 0.19, 90% confidence limits 0.05-0.33) and very likely higher after 19 nights (6.7%, 0.35, 0.10; 0.52).